Quality of Life Following Cochlear Implantation in Patients With Menière's Disease - Sanchez-Cuadrado, Isabel; Calvino, Miryam; Morales-Puebla, Jose Manuel; Gavilán, Javier; Mato, Teresa; Peñarrocha, Julio; Prim, Maria Pilar; Lassaletta, Luis (Frontiers in Neurology, 2021)
Background: Ménière’s disease (MD) is a disorder characterised by auditory and vestibular dysfunction that significantly deteriorates patients’ quality of life (QoL). In addition to the management of vestibular symptoms, some patients with bilateral hearing loss meet criteria for cochlear implantation (CI). Objectives: (1) To assess hearing results and QoL outcomes following CI in patients with MD. (2) To compare these results to a matched control group of patients who had undergone CI. Methods: A retrospective analysis of a study group of 18 implanted patients with MD and a matched control group of 18 implanted patients without MD, who had CI at a tertiary referral center. Hearing and speech understanding were assessed via pure-tone audiometry and disyllabic perception tests in quiet. QoL was assessed via the Nijmegen Cochlear Implant Questionnaire (NCIQ), the Glasgow Benefit Inventory (GBI), the Speech, Spatial and Qualities of Hearing Scale (SSQ12), and the Hearing Implant Sound Quality Index (HISQUI19). The impact of MD ablative surgeries was analyzed in the study group (MD group). Results: Mean preoperative PTA4 thresholds were significantly lower in the MD group (103 dB vs 121 dB). A significant improvement in hearing outcomes was observed following CI in both groups, with a maximum Speech Discrimination Score of 64% and 65% disyllables at 65 dB for the MD and control group, respectively. Subjective outcomes, as measured by the NCIQ, GBI, SSQ12, and HISQUI19 did not significantly differ between groups. In the MD group, despite achieving similar hearing results, QoL outcomes were worse in patients who underwent simultaneous CI and labyrinthectomy. Postoperative NCIQ results were significantly better in patients who had undergone a previous retrosigmoid neurectomy when compared to those who had undergone only CI surgery. Conclusion: Patients with MD and severe hearing loss obtain hearing results and QoL benefits similar to other CI candidates. Delayed CI after labyrinthectomy or vestibular neurectomy can be performed with similar or better results to those of other cochlear implanted patients. Patients who undergo simultaneous CI and labyrinthectomy may achieve similar hearing results but experience worse QoL. Careful preoperative counselling is needed in this subset of patients.